2019
DOI: 10.3390/su11164403
|View full text |Cite
|
Sign up to set email alerts
|

Closed-Loop Supply Chain Network Equilibrium Model with Subsidy on Green Supply Chain Technology Investment

Abstract: The green supply chain (GSC) can effectively reduce the waste of resources and avoid environmental pollution. For a closed-loop supply chain network consisting of multiple manufacturers, multiple retailers, and multiple consumer and recycling markets, we assume that retailers are responsible for the recycling of used products, manufacturers use raw materials to produce new products and recycled products for remanufacturing, and government departments subsidize all manufacturers and retailers for GSC technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Ma et al examined the optimal investment level and cooperation modes in a supply chain and explored how the government policies affect firms' decisions [42]. Wu et al analyzed the optimal technology investment decisions in a green supply chain under government subsidies and found that subsidy policies have a positive effect on the firms' green investment [43].…”
Section: E General Game To Study Government and Enterprisementioning
confidence: 99%
“…Ma et al examined the optimal investment level and cooperation modes in a supply chain and explored how the government policies affect firms' decisions [42]. Wu et al analyzed the optimal technology investment decisions in a green supply chain under government subsidies and found that subsidy policies have a positive effect on the firms' green investment [43].…”
Section: E General Game To Study Government and Enterprisementioning
confidence: 99%
“…Yang et al [31] studied the CLSC network dynamics considering pollution permits. Wu et al [32] analyzed how the government subsidy and the asymmetry of enterprise costs can affect the equilibrium decision-making of the CLSC network. Duan et al [33] considered the impact of consumers' preference and AI-Push on the CLSC network equilibrium.…”
Section: Equilibrium In a Competitive Clsc Networkmentioning
confidence: 99%
“…Fu et al [37] proposed a CLSC network model dealing with heterogeneous products facing different market demands. Existing research work [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] not only obtained CLSC network equilibrium decision-making but also analyzed how external factors, such as random demand, manufacturing level, production period, carbon emission, etc., can affect the equilibrium decision-making. However, all these research works only considered the OEMs' self-remanufacturing policy but did not consider their outsourcing remanufacturing policy.…”
Section: Equilibrium In a Competitive Clsc Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of the scarcity concept as our generality has yet to appear heretofore in literature. The model is also the first to capture the efficacy of fiscal stimulus effort, in contrast to taxes, tariffs, quotas, permits, and item-specific regulations by Nagurney et al (2006Nagurney et al ( , 2019a, Wu et al (2006Wu et al ( , 2019, Yu et al (2018), Nagurney and Dhanda (2000), and Hammond and Beullens (2007).…”
Section: Introductionmentioning
confidence: 99%